The small molecule fenpropimorph rapidly converts chloroplast membrane lipids to triacylglycerols in Chlamydomonas reinhardtii - Kim, Hanul; Jang, Sunghoon; Kim, Sangwoo; Yamaoka, Yasuyo; Hong, Daewoong; Song, Won-Yong; Nishida, Ikuo; Li-Beisson, Yonghua; Lee, Youngsook (Frontiers in Microbiology, 2015)
Concern about global warming has prompted an intense interest in developing economical methods of producing biofuels. Microalgae provide a promising platform for biofuel production, because they accumulate high levels of lipids, and do not compete with food or feed sources. However, current methods of producing algal oil involve subjecting the microalgae to stress conditions, such as nitrogen deprivation, and are prohibitively expensive. Here, we report that the fungicide fenpropimorph rapidly causes high levels of neutral lipids to accumulate in Chlamydomonas reinhardtii cells. When treated with fenpropimorph (10 μg mL–1) for 1 h, Chlamydomonas cells accumulated at least four-fold the amount of triacylglycerols (TAGs) present in the untreated control cells. Furthermore, the quantity of TAGs present after 1 h of fenpropimorph treatment was over two-fold higher than that formed after 9 days of nitrogen starvation in medium with no acetate supplement. Biochemical analysis of lipids revealed that the accumulated TAGs were derived mainly from chloroplast polar membrane lipids. Such a conversion of chloroplast polar lipids to TAGs is desirable for biodiesel production, because polar lipids are usually removed during the biodiesel production process. Thus, our data exemplified that a cost and time effective method of producing TAGs is possible using fenpropimorph or similar drugs.